2000
DOI: 10.1021/ma991197m
|View full text |Cite
|
Sign up to set email alerts
|

A Solid-State 13C NMR Study of the Cure of 13C-Labeled Phenylethynyl End-Capped Polyimides

Abstract: The cure reactions of phenylethynyl end-capped polyimides were investigated using solid-state 13C magic-angle spinning (MAS) nuclear magnetic resonance (NMR). A 13C-labeled model compound (13C-PEPA-3,4‘-ODA) and an imide oligomer (13C-PETI-5) were synthesized and characterized. The thermal cure process for 13C-PEPA-3,4‘-ODA was followed over the temperature range 318−380 °C and for13C-PETI-5 over the temperature range from 350 to 400 °C. Our NMR results showed that, for the model compound, as curing proceeded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 11 publications
(85 reference statements)
4
67
0
Order By: Relevance
“…Previous study has reported that phenylethynyl moiety turns thermally into chain extension, branching and cross-linking through the formation of C=C double bond and that the structure of cross- links were polyene, aromatic ring and so on. 11 The carbonyl stretching vibration is observed at 1680 cm −1 in both spectrum of the uncured and cured compound. This peak has a shoulder at ca.…”
Section: Cross-linking Behavior Of Model Compoundmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous study has reported that phenylethynyl moiety turns thermally into chain extension, branching and cross-linking through the formation of C=C double bond and that the structure of cross- links were polyene, aromatic ring and so on. 11 The carbonyl stretching vibration is observed at 1680 cm −1 in both spectrum of the uncured and cured compound. This peak has a shoulder at ca.…”
Section: Cross-linking Behavior Of Model Compoundmentioning
confidence: 93%
“…[6][7][8][9][10][11][12][13][14][15] It is of importance to design the cross-linkable moiety that crosslinking reaction should occur without the evolution of small volatile compounds to form the clear film and coating. Cross-linkable moieties that meet the required condition are phenylethynyl, cyanate, benzocyclobutane and so on.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] Solid-state 13 C-NMR, FT-IR and ESR analyses have brought some insight into the cure mechanism of arylacetylene group. The results demonstrated that the arylacetylene group underwent cyclotrimerization, hydrogen addition, DielsAlder cycloaddition, etc., and formed a complex crosslinked structure like condensed polycyclic aromatic structure during the cross-linking process.…”
Section: Methodsmentioning
confidence: 99%
“…The following wide exothermic peak (II) occurred in the range from 175 to 275 C. The third exothermic peak (III) appeared at above 300 C. Combined with the FTIR analysis results, the first exothermal peak was attributed to 1,3-dipolar cycloaddition between azide groups and ethynyl or ethynylene groups to form the polymer with 1,4-disubmitted and 1,5-disubmitted 1,2,3-triazoles. The second peak related to the polymerization of ethynyl of ethynylene to form polyene, benzene ring, and naphthalene ring, 18 and the third peak attributed to polymerization of ethynylene, as well as decomposition of cured resin successively, as shown in Scheme 1. Figure 4 shows the 13 C CP/MAS spectra of the PDMSEPE-DAMBP samples cured at 80 C for 12 h or then postcured at 250 C. The peaks at 74.18 and 79.10 ppm were attributed to the ethynyl group and 90.19, 103.08 ppm were assigned to the ethynylene group.…”
mentioning
confidence: 99%